HSP90.2 modulates 2Q2‐mediated wheat resistance against powdery mildew. (20th March 2023) - Yan, Yan; Guo, Yue‐Ting; Chang, Chao‐Yan; Li, Xiao‐Ming; Zhang, Mei‐Qi; Ding, Ci‐Hang; Cui, Dangqun; Sun, Congwei; Ren, Yan; Wang, Meng‐Lu; Xie, Chaojie; Ni, Zhongfu; et al.
Abstract: Wheat ( Triticum aestivum L.) is a critical food crop feeding the world, but pathogens threaten its production. Wheat Heat Shock Protein 90.2 (HSP90.2) is a pathogen‐inducible molecular chaperone folding nascent preproteins. Here, we used wheat HSP90.2 to isolate clients regulated at the posttranslational level. Tetraploid wheat hsp90.2 knockout mutant was susceptible to powdery mildew, while the HSP90.2 overexpression line was resistant, suggesting that HSP90.2 was essential for wheat resistance against powdery mildew. We next isolated 1500 clients of HSP90.2, which contained a wide variety of clients with different biological classifications. We utilized 2Q2, a nucleotide‐binding leucine repeat‐rich protein, as a model to investigate the potential of HSP90.2 interactome in fungal resistance. The transgenic line co‐suppressing 2Q2 was more susceptible to powdery mildew, suggesting 2Q2 as a novel Pm ‐resistant gene. The 2Q2 protein resided in chloroplasts, and HSP90.2 played a critical role in the accumulation of 2Q2 in thylakoids. Our data provided over 1500 HSP90.2 clients with a potential regulation at the protein folding process and contributed a nontypical approach to isolate pathogenesis‐related proteins. Summary Statement: This work revealed over 1500 clients of wheat Heat Shock Protein 90.2, a highly conserved pathogen molecular chaperone folding a wide range of signal transducers. 2Q2, a chloroplast‐localized nucleotide‐binding leucine repeat‐rich (NB‐LRR) protein, was discovered as a novel powdery mildew‐resistant protein, showing the potential of HSP90.2 chaperome in future plant fungal resistance study.